The acceptance of mixed methods in business and management research - Cameron, Roslyn; Molina-Azorin, J. (Emerald Group Publishing Limited, 2011)
Purpose – The purpose of this study is to examine the prevalence of mixed methods research acrossseveral business and management fields and to gauge the level of acceptance of mixed methods withinthese fields.Design/methodology/approach – The methodology employed for this study involved synthesizingthe findings from six large-scale methodological scans of business and management discipline journalsin seven fields: marketing, international business, strategic management, organizational behaviour,operations management, entrepreneurship and human resource management.Findings – The study finds that quantitative studies dominate all seven fields (76 per cent ofempirical articles) followed by mixed methods (14 per cent of empirical articles) and qualitative studies(10 per cent of empirical articles). In applying the framework for acceptance levels, it would seem thereexists minimal acceptance of mixed methods across these fields.Research limitations/implications – The study has limitations related to the coverage of differentdisciplines and differences in sample sets. More extensive research is planned for the future and willinvolve an expanded mixed method prevalence rate study across additional business and managementfields.Practical implications – The growing use of mixed methods has practical implications for researchtraining and capacity building within business schools. The study points to the need to developresearch capacity through the introduction of postgraduate courses in mixed methods and advancedresearch skills training for existing researchers.Originality/value – Mixed methods is a relatively new and emerging methodological movement.This paper attempts to gauge the use and level of acceptance of mixed methods across a diverse rangeof business and management discipline areas.